Monitoring dan Evaluasi Kinerja Karyawan menggunakan Algoritma Simple Additive Weighting dan Hungarian - Gunawan, Wawan; Firmansyah, Muhammad Riski (ILKOM Jurnal Ilmiah, 2020)
Monitoring and evaluating the performance of  employees of PT Akulaku Silvrr Indonesia still use microsoft excel application online,   which has some weaknesses, which is an obstacle in monitoring is that  adalah it is unable to give specific job orders    and can not provide due date information,whereas  in determining the provision of salary increase and employee benefits is done randomly and only based on the last education. Tohelp the company succeed in achieving its goals, a system can be needed that can help in making decisions on a large or small scale. The  use of Simple Additive Weighting  (SAW) method can be used to determine pay raises and incentivize precisely and accurately  based on the specified criteria, while hungarian method is used to determine who will do the job at a difficult, easy and moderate level. So the rating for the salary increase for the support team is Andi Ansyah, Hangga Bagus, Chikal Aviv and Ray Awaludin. Determining the next task can be determined that Andi Ansyah can do the job easily and difficultly, Hangga Bagus can do the job easily and moderately, Chikal Aviv can do a medium and difficult job. While Ray Awaludin does not have the highest value for each job, so it is necessary to be given training.